Potensi Ekstrak Makroalga Watercress sebagai Anti Bakteri Aeromonas hydrophila secara in vitro - Qurrota A'yunin; Dinarti Dinarti; Nurhabibah Nurhabibah; Budianto Budianto (Jurnal Sumberdaya Akuatik Indopasifik, 2021)
Disease infection is a problem in catfish farming. The diseases that often arise in catfish farming is Motile Aeromonas Septicemia (MAS). It can infect the catfish group with a high mortality rate. Watercress extract is thought to inhibit the growth of pathogenic bacteria that infect catfish. Bacteria that infect catfish are cultured and biochemically identified. The extracts test was carried out through an inhibition tests with different doses to determine the activity of extracts in inhibiting bacterial growth. Based on the results of biochemical identification, the pathogenic bacteria that infect catfish are Aeromonas hydrophila. The results of the inhibition test showed that a dose of 70 ppm had the highest inhibitory response compared to other doses. This indicates that watercress macroalgae extract can inhibit the growth of pathogenic bacteria so it can be used as an alternative medicine to treat Aeromonas hydrophila infection in fish.